LDLR variants functional characterization: Contribution to variant classification. (July 2021) - Alves, Ana Catarina; Azevedo, Sílvia; Benito-Vicente, Asier; Graça, Rafael; Galicia-Garcia, Unai; Barros, Patrícia; Jordan, Peter; Martin, Cesar; Bourbon, Mafalda
Abstract: Background and aims: Familial hypercholesterolaemia (FH) is an autosomal disorder of lipid metabolism presenting with increased cardiovascular risk. LDLR mutations are the cause of disease in 90% of the cases but functional studies have only been performed for about 15% of all LDLR variants. In the Portuguese Familial Hypercholesterolemia Study (PFHS), 142 unique LDLR alterations were identified and 44 (30%) lack functional characterization. The aim of the present work is to increase evidence for variant classification by performing functional characterization of 13 LDLR missense alterations found in Portugal and in 20 other countries. Methods: Different LDLR mutants were generated by site-directed mutagenesis and expressed in CHO–ldlA7 cells lacking endogenous expression of LDLR. To determine the effects of alterations on LDLR function, cell surface expression, binding and uptake of FITC-LDL were assessed by flow cytometry and Western blot. Results: Of the 13 variants studied 7 were shown to affect LDLR function - expression, binding or uptake, with rates lower than 60%: p.(Cys184Tyr), p.(Gly207_Ser213del); p.(His211Asp); p.(Asp221Tyr); p.(Glu288Lys); p.(Gly592Glu) and p.(Asp601Val)). The remaining 6 variants do not alter the LDLR function. Conclusions: These studies contributed to an update of these variants classification: from the 9 variants classified as variants of unknown significance, 7 have reached now a final classification and 3 variants have improved classification from likely pathogenic to pathogenic. In Portugal, an additional 55 patients received an FH definite diagnosis thanks to these studies. Since only likely pathogenic and pathogenic variants are clinically actionable, this work shows the importance of functional studies for variant classification. Graphical abstract: Image 1 Highlights: This work shows the importance of functional studies for variant classification, since only likely pathogenic and pathogenic variants are clinically actionable. This work contributed to an update of 10 variants classification. Variants presented in this work were also found in 20 different countries and many other patients worldwide will benefit from these. Functional studies are very important to add evidence to reach a final classification with the ACMG algorithm.